IMMEDIATE RESULTS OF ENDOVASCULAR AND LITTLE INVASIVE METHODS OF TREATMENT OF LUNG PURULENT DISEASES WITH DIABETES MELLITUS - Khamdamov, Sh.A.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Conducting longterm intraarterial catheter therapy in patients with purulent-necrotic lesions of the foot in diabetes mellitus significantly improved the results of treatment, reduced the number of high amputations of the lower extremities to 2.7% and avoided early recurrence of purulent-necrotic process in the lungs.